2020
DOI: 10.3390/su12062535
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Wood Decaying Fungi Diversity in Central Siberia, Russia Using ITS Sequence Analysis and Interaction with Host Trees

Abstract: Wood-decay fungi (WDF) play a significant role in recycling nutrients, using enzymatic and mechanical processes to degrade wood. Designated as a biodiversity hot spot, Central Siberia is a geographically important region for understanding the spatial distribution and the evolutionary processes shaping biodiversity. There have been several studies of WDF diversity in Central Siberia, but identification of species was based on morphological characteristics, lacking detailed descriptions and molecular data. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
1
11
1
1
Order By: Relevance
“…Birch, poplar, and willow trees were the preferential hosts for Bjerkandera adusta, Cerrena unicolor, Phlebia spp. andTrametes hirsuta [65], the fungal species also found in this study and reported as endophytes from multiple hosts [66]. There is a lack of available nitrogen in wood and, therefore, nematophagous fungi (which showed good ability to colonize wood) satisfy their nitrogen requirements by capturing nematodes [7].…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Birch, poplar, and willow trees were the preferential hosts for Bjerkandera adusta, Cerrena unicolor, Phlebia spp. andTrametes hirsuta [65], the fungal species also found in this study and reported as endophytes from multiple hosts [66]. There is a lack of available nitrogen in wood and, therefore, nematophagous fungi (which showed good ability to colonize wood) satisfy their nitrogen requirements by capturing nematodes [7].…”
Section: Resultssupporting
confidence: 63%
“…It was not unexpected that the plant parasitic fungi might occur in crops and subsequently they could be transferred to soil. In contrast, the species of the phylum Basidiomycota ( Phlebia nothofagi , Phlebiopsis ravenelii , Bjerkandera adusta , Trametes hirsuta , and Cerrena unicolor ) were reported to be associated with birch, poplar, and willow forest ecosystems [ 65 ], but their presence was surprising in agricultural soil of the Pannonian Plain. The explanation was found through the analysis of historical data.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that plant immunity could be reduced because larvae feed on the phloem of trees by creating serpentine galleries, thus preventing nutrient movement. The transition from twig infestation to twig death thus creates the growth of saprophytic wood decaying fungi (WDF) [45,46]. Lignin is known to be extensively degraded by WDF and other fungi [45,46]; therefore, A. mali larvae gut bacteria specialized in degradation of cellulose but not lignin.…”
Section: Discussionmentioning
confidence: 99%
“…The transition from twig infestation to twig death thus creates the growth of saprophytic wood decaying fungi (WDF) [45,46]. Lignin is known to be extensively degraded by WDF and other fungi [45,46]; therefore, A. mali larvae gut bacteria specialized in degradation of cellulose but not lignin. Moreover, the lignin composition and content vary between xylem and phloem [47].…”
Section: Discussionmentioning
confidence: 99%
“…While the ectomycorrhizal species composition in Korea is very different from those of Europe and North America [ 16 , 17 ], there is little difference between saprotrophic fungi compositions between continents [ 46 , 47 ]. Correspondingly, we confirmed that the Korean Pholiota species showed little genetic difference from the European and North American Pholiota species in the ITS neighbor-joining (NJ) phylogeny ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%